Metal vs. ligand protonation and the alleged proton-shuttling role of the azadithiolate ligand in catalytic H2 formation with FeFe hydrogenase model complexes. Issue 21 (7th May 2019) - Aster, Alexander; Wang, Shihuai; Mirmohades, Mohammad; Esmieu, Charlène; Berggren, Gustav; Hammarström, Leif; Lomoth, Reiner
Abstract : Real-time spectroscopic observation of electron transfer-induced protonation reactivity elucidates the role of the second sphere basic site in a H2 evolution catalyst. Abstract : Electron and proton transfer reactions of diiron complexes [Fe2 adt(CO)6 ] (1 ) and [Fe2 adt(CO)4 (PMe3 )2 ] (4 ), with the biomimetic azadithiolate (adt) bridging ligand, have been investigated by real-time IR- and UV-vis-spectroscopic observation to elucidate the role of the adt-N as a potential proton shuttle in catalytic H2 formation. Protonation of the one-electron reduced complex, 1 −, occurs on the adt-N yielding1H and the same species is obtained by one-electron reduction of1H + . The preference for ligand vs. metal protonation in the Fe2 (i, 0) state is presumably kinetic but no evidence for tautomerization of1H to the hydride1Hy was observed. This shows that the adt ligand does not work as a proton relay in the formation of hydride intermediates in the reduced catalyst. A hydride intermediate1HHy + is formed only by protonation of1H with stronger acid. Adt protonation results in reduction of the catalyst at much less negative potential, but subsequent protonation of the metal centers is not slowed down, as would be expected according to the decrease in basicity. Thus, the adtH + complex retains a high turnover frequency at the lowered overpotential. Instead of proton shuttling, we propose that this gain in catalytic performance compared to the propyldithiolate analogue might be rationalized in terms of lower reorganization energy for hydride formation with bulk acid upon adt protonation.